Preliminary validation of turbulent flow through an orifice meter / A. H. A. Hamid ... [et al.] - A. H. A., Hamid; M. S. M., Sharom; M. R. M., Nawi; H., Hamdan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
An orifice meter is a device to measure the rate of fluid flow in a pipe by recording the pressure difference upstream and downstream of the meter. Due to the sensitive nature of orifice meter on the upstream flow conditions, measuring the pressure drop and determining the discharge coefficient pose a challenge and may possibly yield a large deviation. The present work intends to establish a numerical procedure verified with experiment results from ISO 5167-2 standard to evaluate the pressure drop and thus the discharge coefficient of orifice plates. An open source CFD simulation software is employed to simulate the steady-state turbulent flows with a fully developed velocity profile imposed at the pipe inlet. The numerical analysis revealed discharge coefficient errors of less than 4% when compared with experiment data. Following this analysis, three new concepts of orifice meter are introduced, with the goal to minimize the sensitivity to the upstream flow conditions and thus improve measurement accuracy.